Ativismo judicial: o papel dos juizes num paradigma constitucionalmente adequado - Ribeiro, Isabela Lessa de Azevedo Pinto (2008)
We live in a time of redefinition of the significant, building new concepts ad equating with the complexity of modern life. In the same way, the comprehension we have from the jurisdiction is in a delay with the real transformation happened between the knowledge of modernity- secularization of law and the bourgeoisie revolutions- and the present date. The recognizing of the human character from the science of comprehension- hermeneutic- as well as the historical development of the human being lead us to question what is the judicial activism. We start analysing the separation of power mechanism who granted the political liberation, besides bourgeoisie liberty of thought, that therefore are constitutionals guarantees as individual rights. The second world war created a new concern about the implementation of fundamental rights, that since the begging of the twentieth century, thru the social rights, men`s economical liberation and brings the law`s sovereignty to crisis, therefore it`s evident the emergence of a review on the three powers theory since the greater effectiveness of those rights allowed a greater judicial control of the others powers, changing our pre-comprehension of judicature. Hence, the judicial activism is the doctrine defending a judicial activity not neutral but committed with the higher constitutional state - not more only democratic - intersubjective value: fundamental rights and a dignifying human condition